Tuning the electrical performance of metal oxide thin-film transistors via dielectric interface trap passivation and graded channel modulation doping. Issue 5 (19th January 2017) - Wu, Zhiheng; Yao, Zhiqiang; Liu, Suilin; Yuan, Bin; Zhang, Yake; Liang, Yu; Wang, Zhuo; Tang, Xiaosheng; Shao, Guosheng
Abstract : A novel strategy to achieve high performance thin-film transistors based on carrier concentration-graded InGaZnO channels using Al2 O3 -passivated HfO2 as a dielectric layer was established. Abstract : Passivating trap defects and controlling carrier concentration and doping profiles in the functional dielectric and channel layers is a prerequisite for designing high performance electronic devices. Here, we investigate the effects of dielectric interface trap passivation and graded channel modulation doping on the electrical performance of InGaZnO thin-film transistors (TFTs). The introduction of ultrathin Al2 O3 passivation layers up to 2 nm in thickness sandwiched between HfO2 thin films allows efficient suppression of hysteresis in InGaZnO TFTs. IGZO TFTs with graded channel doping profiles were constructed by consecutive modulation of oxygen partial pressure without growth interruption. Enhancement-mode InGaZnO TFTs with high performance are fabricated by limiting the depth of the high carrier concentration gradient InGaZnO films to as thin as only a few angstroms. The graded channel structure InGaZnO TFTs shows consistently excellent characteristics including a large saturation mobility of 112.8 cm 2 V −1 s −1, small subthreshold swing of 82.6 mV dec −1, low threshold voltage of 0.28 V, and high on/off current ratios >2.0 × 10 9, which are comparable to those of the commercial low-temperature poly-silicon TFTs. Most importantly, the as-fabricated InGaZnO TFTs show robust current controlling capacities for high-power light emitting diode arrays. This work represents a major step toward the development of high-performance oxide electronics.